A preparation method of nylon 66 material

A method combining modified polypropylene fiber and polytetrafluoroethylene with additives in a twin-screw extrusion process enhances the mechanical and chemical resistance of nylon 66 materials, addressing high-temperature and environmental challenges.

CN118109046BActive Publication Date: 2024-12-17BINZHOU ZHONGKE CATALYTIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410231705.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-29
Publication Date
2024-12-17
Estimated Expiration
2044-02-29

AI Technical Summary

Technical Problem

Nylon 66 materials exhibit poor high-temperature resistance and poor acid and alkali resistance, limiting their application in harsh environments.

Method used

A method involving the use of modified polypropylene fiber, polytetrafluoroethylene, and specific additives, combined with a dispersant, is used to prepare nylon 66 materials through a twin-screw extrusion process, enhancing mechanical properties, thermal stability, and resistance to acids and alkalis.

Benefits of technology

The resulting nylon 66 material demonstrates improved tensile properties, thermal stability, and resistance to both acidic and alkaline environments, suitable for chemical equipment applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118109046B_ABST
    Figure CN118109046B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a nylon 66 material, comprising the following steps: (1) placing modified polypropylene fiber, polytetrafluoroethylene, an additive and nylon 66 resin in a high-speed mixer and mixing them evenly to obtain a mixed material; (2) mixing the mixed material mixed in step (1) and a dispersant again and placing them in a twin-screw extruder for extrusion granulation to obtain a nylon 66 material. The method adds modified polypropylene fiber, polytetrafluoroethylene and an additive, and through reasonable compounding, the prepared nylon 66 material has good tensile properties, thermal stability and acid and alkali resistance, and is very suitable for the field of chemical equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer material preparation, and in particular to a method for preparing nylon 66 material. Background Art

[0002] Nylon 66 is one of the earliest developed, largest-volume, and most widely used nylon products. It is a thermoplastic resin formed by the polycondensation of adipic acid and hexamethylenediamine. It is colorless and transparent and is a polycrystalline semi-crystalline polymer. Nylon 66 has a large number of polar amide bonds on its molecular chain, which easily absorbs water to form hydrogen bonds in the main chain and is easily oriented. As an engineering plastic, nylon 66 has excellent properties such as good mechanical properties, oil resistance, wear resistance, and self-lubrication. It is often used in automobiles, electronic and electrical, packaging materials, etc. In addition, it is also widely used in cosmetics, adhesives and other fields.

[0003] For nylon 66 materials, due to its poor long-term heat aging resistance, the material will degrade significantly under high temperature processing conditions and harsh use environments. At present, the main way to improve the heat aging resistance of nylon 66 is to blend the prepared nylon 66 with antioxidants, heat stabilizers, etc., so as to improve the heat aging resistance of nylon 66. Patent CN201210295603.X discloses a moderately rigid and tough anti-aging lubricating nylon 66 material, which uses inorganic powder, wear-resistant agent, toughening agent, anti-aging aid, internal lubrication processing aid, etc. to compositely modify the nylon 66 material, at least including (by weight percentage) nylon 66-100 parts; toughening agent 5-25 parts; talcum powder 5-50 parts; molybdenum disulfide 2-10 parts; channel carbon black 2-5 parts. The material has excellent tribological properties, physical and mechanical properties and anti-aging properties. The nylon 66 material prepared by this process has good anti-aging properties, but its high temperature resistance needs to be improved.

[0004] Patent CN202010128564.9 discloses a thermally conductive nylon 66 material and a preparation method thereof, which is prepared by 69.1-89.8% nylon 66, 10-30% thermal conductivity modifier, 0.1-0.3% lubricant and 0.1-0.6% antioxidant according to weight percentage, wherein the thermal conductivity modifier is 4,4′-dihydroxybiphenyl modified nylon, and the 4,4′-dihydroxybiphenyl modified nylon is prepared by reflux reaction of nylon 66 and 4,4′-dihydroxybiphenyl with potassium carbonate in DMF solution. The nylon 66 material has better mechanical properties while achieving thermal conductivity. In actual use, the better the performance of nylon materials, the more they can be applied to various fields with harsh conditions, such as acidic water or alkaline water and other substances may exist in the reaction equipment of some refineries or chemical plant workshops, which requires that various materials used in related equipment need to be able to withstand acidity and alkalinity. Summary of the invention

[0005] In view of the problems that the high temperature resistance of synthetic nylon 66 materials in the prior art needs to be improved and the acid and alkali resistance is poor, the present invention provides a method for preparing nylon 66 materials.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A method for preparing nylon 66 material comprises the following steps:

[0008] (1) placing modified polypropylene fiber, polytetrafluoroethylene, an additive and nylon 66 resin in a high-speed mixer and mixing them evenly to obtain a mixed material; (2) mixing the mixed material mixed in step (1) and a dispersant again and placing them in a twin-screw extruder for extrusion granulation to obtain a nylon 66 material. Furthermore, the modified polypropylene fiber, polytetrafluoroethylene, an additive and nylon 66 resin are calculated by weight: 40-58 parts of nylon 66 resin, 2-10 parts of polytetrafluoroethylene, 0.1-3 parts of the additive, and 13-25 parts of the modified polypropylene fiber.

[0009] Furthermore, the mass of the dispersant is 1-3% of the mass of the mixed material, and the dispersant is sodium pyrophosphate and polyethylene glycol 400.

[0010] Furthermore, the preparation method of the modified polypropylene fiber is:

[0011] Sodium metasilicate, urea and deionized water are prepared into a mixed solution, polypropylene fiber is placed in the mixed solution, and then placed in a stainless steel reactor for treatment at 100-120°C for 4-7 hours. After the treatment is completed, the fiber is taken out, cooled to room temperature and dried for later use.

[0012] Furthermore, the mass ratio of the sodium metasilicate to urea is 100:1-6.

[0013] Furthermore, the auxiliary agent includes isooctyl salicylate, diphenyl phosphoazide, 1,2-propylene glycol, mica and calcium stearate. Furthermore, the mass ratio of isooctyl salicylate, diphenyl phosphoazide, 1,2-propylene glycol, mica and calcium stearate is 100:1-8:15-36:0.1-1:5-10.

[0014] Furthermore, the temperature of the twin-screw extruder is 360-370°C, the screw speed is 90-120 r / min, the feed speed is 10-15 r / min, melt extrusion, water cooling, stranding and pelletizing are performed to obtain nylon 66 material. The nylon 66 material obtained according to the above preparation method.

[0015] The application of nylon 66 material obtained according to the above preparation method in the field of chemical equipment.

[0016] The present invention has the following beneficial effects:

[0017] 1. The nylon 66 material provided by the present invention is based on the original nylon 66 resin and modified polypropylene fiber is added, which effectively improves the tensile properties of the nylon 66 material and greatly improves the mechanical properties of the nylon 66 material; by adding polytetrafluoroethylene and additives and performing reasonable compounding, the acid and alkali resistance and thermal stability of the nylon 66 material are effectively improved, which can fully meet the high stability application requirements of plastic materials for products such as coil skeletons and sealing rings used in chemical plant equipment, and has good market application value.

[0018] 2. The nylon 66 material provided by the present invention can well mix the materials by adding a dispersant during the mixing process, so that the modified polypropylene fiber, polytetrafluoroethylene and additives can be fully dispersed, thereby avoiding the difference in performance of the subsequent same batch of nylon 66 materials caused by uneven mixing of materials during the melting process.

[0019] 3. The preparation method of nylon 66 material provided by the present invention has easy-to-obtain raw material components and a simple preparation process, thereby effectively reducing the preparation cost of the entire nylon 66 material. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a graph showing the thermal deformation temperature test results of the nylon 66 material provided by the present invention. DETAILED DESCRIPTION

[0021] The preparation method of nylon 66 material provided by the present invention comprises: (1) placing modified polypropylene fiber, polytetrafluoroethylene, an additive and nylon 66 resin in a high-speed mixer and mixing them uniformly to obtain a mixed material; (2) mixing the mixed material and a dispersant mixed uniformly in step (1) again and placing them in a twin-screw extruder for extrusion granulation to obtain nylon 66 material.

[0022] According to the method provided by the present invention, in a preferred case, the method for modifying polypropylene fiber is: preparing a solution containing sodium metasilicate and urea, the solvent is deionized water, and then the polypropylene fiber is placed in the prepared solution, and then placed in a stainless steel reactor for treatment at 100-120°C for 4-7h, after the treatment is completed, it is taken out and cooled to room temperature and dried for use, wherein the mass ratio of sodium metasilicate to urea is 100:1-6, and the specific drying can be carried out in a common oven, and the drying conditions are drying at 90°C for 2 hours.

[0023] According to the method provided by the present invention, in a preferred case, the modified polypropylene fiber, polytetrafluoroethylene, additives and nylon 66 resin are calculated by weight: 40-58 parts of nylon 66 resin, 2-10 parts of polytetrafluoroethylene, 0.1-3 parts of additives, and 13-25 parts of modified polypropylene fiber.

[0024] According to the method provided by the present invention, in a preferred case, the mass of the dispersant is 1-3% of the mass of the mixed material, and the dispersant is sodium pyrophosphate and polyethylene glycol 400. Here, the mass ratio of sodium pyrophosphate and polyethylene glycol 400 in the dispersant can be used when the total mass is determined. The amount of sodium pyrophosphate and polyethylene glycol 400 has little effect on the subsequent preparation process and the performance of the obtained nylon 66 material, but it is preferred that both are used as dispersants at the same time, and the purpose is only to facilitate the full dispersion of each component in nylon 66 and make them mix evenly.

[0025] According to the method provided by the present invention, in a preferred embodiment, the auxiliary agent includes isooctyl salicylate, diphenylphosphoryl azide, 1,2-propylene glycol, mica and calcium stearate.

[0026] According to the method provided by the present invention, in a preferred case, the mass ratio of isooctyl salicylate, diphenylphosphoryl azide, 1,2-propylene glycol, mica and calcium stearate is 100:1-8:15-36:0.1-1:5-10.

[0027] According to the method provided by the present invention, in a preferred case, the temperature of the twin-screw extruder is 360-375°C, the screw speed is 90-120r / min, the feeding speed is 10-15r / min, the side feeding speed is 15r / min, the side feeding speed is 10r / min, the melt extrusion, water-cooled drawing and pelletizing are obtained to obtain nylon 66 material.

[0028] According to the method provided by the present invention, in a preferred case, the temperatures of the first to eighth zones of the twin-screw extruder are respectively set to 360° C., 365° C., 375° C., 370° C., 375° C., 370° C., 375° C., 370° C. Changing the temperature of each zone of the twin-screw extruder will significantly affect the various properties of the final nylon 66 material.

[0029] Nylon 66 material prepared by the method provided by the present invention.

[0030] According to the method provided by the present invention, the method further comprises water-cooling and granulating the final extruded material and then drying it to obtain a product, and the drying temperature is 85-95°C.

[0031] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments.

[0032] The chemical reagents described in the following embodiments of the present invention, such as sodium metasilicate, urea, isooctyl salicylate, diphenyl phosphoazide and 1,2-propylene glycol, etc., can be purchased directly from the market. The nylon 66 resin used is purchased from Zhejiang Huafeng Synthetic Resin Co., Ltd., item number EP158.

[0033] Example 1

[0034] Preparation of modified polypropylene fiber

[0035] A modified solution was prepared according to the mass ratio of sodium metasilicate and urea of ​​100:6, and the solvent was deionized water. Then, polypropylene fiber (purchased from Tianyi Engineering Fiber Co., Ltd., polypropylene monofilament fiber) was immersed in the prepared modified solution, and then placed in a stainless steel reactor for treatment at 110°C for 5 hours. After the treatment was completed, it was taken out and cooled to room temperature, and then placed in an oven for drying at 90°C for 2 hours for use.

[0036] Preparation of nylon 66 material

[0037] First, the modified polypropylene fiber, polytetrafluoroethylene, additives and nylon 66 resin are mixed in a weight ratio of 50 parts of nylon 66 resin, 2 parts of polytetrafluoroethylene, 1 part of additives, and 15 parts of modified polypropylene fiber, wherein the additives are isooctyl salicylate, diphenyl phosphoazide, 1,2-propylene glycol, mica and calcium stearate, and the corresponding mass ratio is 100:5:20:1:5. The above materials are placed in a high-speed mixer for 5 minutes and mixed evenly to obtain a mixed material.

[0038] Sodium pyrophosphate and polyethylene glycol 400 are weighed as dispersants, wherein the total mass of sodium pyrophosphate and polyethylene glycol 400 is 3% of the total mass of the above-mentioned uniformly mixed mixture, and the mass ratio of sodium pyrophosphate to polyethylene glycol 400 is 1:1. The mixture and the dispersant are mixed again for 2 minutes, and then placed in a twin-screw extruder for heating and melting. After extrusion, the mixture is water-cooled, stretched and pelletized, and dried at 85°C to obtain a nylon 66 material.

[0039] The operating parameters of the twin-screw extruder are set as follows: the temperatures of zones one to eight of the twin-screw extruder are set to 360°C, 365°C, 375°C, 370°C, 375°C, 370°C, 375°C, 370°C, respectively, the head temperature is adjusted to 370°C, the screw speed is 90-120r / min, the feeding speed is 15r / min, and the side feeding speed is 10r / min.

[0040] Example 2

[0041] Preparation of modified polypropylene fiber

[0042] A modified solution was prepared according to the mass ratio of sodium metasilicate and urea of ​​100:1, and the solvent was deionized water. Then, polypropylene fiber (purchased from Tianyi Engineering Fiber Co., Ltd., polypropylene monofilament fiber) was immersed in the prepared modified solution, and then placed in a stainless steel reactor for treatment at 120°C for 4 hours. After the treatment was completed, it was taken out and cooled to room temperature, and then placed in an oven for drying at 90°C for 2 hours for use.

[0043] Preparation of nylon 66 material

[0044] First, the modified polypropylene fiber, polytetrafluoroethylene, additives and nylon 66 resin are mixed in a weight ratio of 50 parts of nylon 66 resin, 2 parts of polytetrafluoroethylene, 1 part of additives, and 15 parts of modified polypropylene fiber, wherein the additives are isooctyl salicylate, diphenyl phosphoazide, 1,2-propylene glycol, mica and calcium stearate, and the corresponding mass ratio is 100:5:20:1:5. The above materials are placed in a high-speed mixer for 5 minutes and mixed evenly to obtain a mixed material.

[0045] Sodium pyrophosphate and polyethylene glycol 400 are weighed as dispersants, wherein the total mass of sodium pyrophosphate and polyethylene glycol 400 is 3% of the total mass of the above-mentioned uniformly mixed mixture, and the mass ratio of sodium pyrophosphate to polyethylene glycol 400 is 1:1. The mixture and the dispersant are mixed again for 2 minutes, and then placed in a twin-screw extruder for heating and melting. After extrusion, the mixture is water-cooled, stretched and pelletized, and dried at 85°C to obtain a nylon 66 material.

[0046] The operating parameters of the twin-screw extruder are set as follows: the temperatures of zones one to eight of the twin-screw extruder are set to 360°C, 365°C, 375°C, 370°C, 375°C, 370°C, 375°C, 370°C, respectively, the head temperature is adjusted to 370°C, the screw speed is 90-120r / min, the feeding speed is 15r / min, and the side feeding speed is 10r / min.

[0047] Example 3

[0048] Preparation of modified polypropylene fiber

[0049] A modified solution was prepared according to the mass ratio of sodium metasilicate and urea of ​​100:6, and the solvent was deionized water. Then, polypropylene fiber (purchased from Tianyi Engineering Fiber Co., Ltd., polypropylene monofilament fiber) was immersed in the prepared modified solution, and then placed in a stainless steel reactor for treatment at 120°C for 4 hours. After the treatment was completed, it was taken out and cooled to room temperature, and then placed in an oven for drying at 90°C for 2 hours for use.

[0050] Preparation of nylon 66 material

[0051] First, the modified polypropylene fiber, polytetrafluoroethylene, additives and nylon 66 resin are mixed in a weight ratio of 40 parts of nylon 66 resin, 10 parts of polytetrafluoroethylene, 1 part of additives, and 20 parts of modified polypropylene fiber, wherein the additives are isooctyl salicylate, diphenyl phosphoazide, 1,2-propylene glycol, mica and calcium stearate, and the corresponding mass ratio is 100:1:36:1:8. The above materials are placed in a high-speed mixer for 5 minutes and mixed evenly to obtain a mixed material.

[0052] Sodium pyrophosphate and polyethylene glycol 400 are weighed as dispersants, wherein the total mass of sodium pyrophosphate and polyethylene glycol 400 is 3% of the total mass of the above-mentioned uniformly mixed mixture, and the mass ratio of sodium pyrophosphate to polyethylene glycol 400 is 1:1. The mixture and the dispersant are mixed again for 2 minutes, and then placed in a twin-screw extruder for heating and melting. After extrusion, the mixture is water-cooled, stretched and pelletized, and dried at 85°C to obtain a nylon 66 material.

[0053] The operating parameters of the twin-screw extruder are set as follows: the temperatures of zones one to eight of the twin-screw extruder are set to 360°C, 365°C, 375°C, 370°C, 375°C, 370°C, 375°C, 370°C, respectively, the head temperature is adjusted to 370°C, the screw speed is 90-120r / min, the feeding speed is 15r / min, and the side feeding speed is 10r / min.

[0054] Example 4

[0055] Preparation of modified polypropylene fiber

[0056] A modified solution was prepared according to the mass ratio of sodium metasilicate and urea of ​​100:6, and the solvent was deionized water. Then, polypropylene fiber (purchased from Tianyi Engineering Fiber Co., Ltd., polypropylene monofilament fiber) was immersed in the prepared modified solution, and then placed in a stainless steel reactor for treatment at 120°C for 4 hours. After the treatment was completed, it was taken out and cooled to room temperature, and then placed in an oven for drying at 90°C for 2 hours for use.

[0057] Preparation of nylon 66 material

[0058] First, the modified polypropylene fiber, polytetrafluoroethylene, additives and nylon 66 resin are mixed in a weight ratio of 58 parts of nylon 66 resin, 10 parts of polytetrafluoroethylene, 0.1 parts of additives, and 13 parts of modified polypropylene fiber, wherein the additives are isooctyl salicylate, diphenyl phosphoazide, 1,2-propylene glycol, mica and calcium stearate, and the corresponding mass ratio is 100:8:15:0.1:10. The above materials are placed in a high-speed mixer for 5 minutes and mixed evenly to obtain a mixed material.

[0059] Sodium pyrophosphate and polyethylene glycol 400 are weighed as dispersants, wherein the total mass of sodium pyrophosphate and polyethylene glycol 400 is 1% of the total mass of the above-mentioned uniformly mixed mixture, and the mass ratio of sodium pyrophosphate and polyethylene glycol 400 is 1:1. The mixture and the dispersant are mixed again for 2 minutes, and then placed in a twin-screw extruder for heating and melting. After extrusion, the mixture is water-cooled, stretched and pelletized, and dried at 85°C to obtain a nylon 66 material.

[0060] The operating parameters of the twin-screw extruder are set as follows: the temperatures of zones one to eight of the twin-screw extruder are set to 360°C, 365°C, 375°C, 370°C, 375°C, 370°C, 375°C, 370°C, respectively, the head temperature is adjusted to 370°C, the screw speed is 90-120r / min, the feeding speed is 15r / min, and the side feeding speed is 10r / min.

[0061] Example 5

[0062] Preparation of modified polypropylene fiber

[0063] A modified solution was prepared according to the mass ratio of sodium metasilicate and urea of ​​100:1, and the solvent was deionized water. Then, polypropylene fiber (purchased from Tianyi Engineering Fiber Co., Ltd., polypropylene monofilament fiber) was immersed in the prepared modified solution, and then placed in a stainless steel reactor for treatment at 120°C for 4 hours. After the treatment was completed, it was taken out and cooled to room temperature, and then placed in an oven for drying at 90°C for 2 hours for use.

[0064] Preparation of nylon 66 material

[0065] First, the modified polypropylene fiber, polytetrafluoroethylene, additives and nylon 66 resin are mixed in a weight ratio of 58 parts of nylon 66 resin, 10 parts of polytetrafluoroethylene, 3 parts of additives, and 25 parts of modified polypropylene fiber, wherein the additives are isooctyl salicylate, diphenyl phosphoazide, 1,2-propylene glycol, mica and calcium stearate, and the corresponding mass ratio is 100:8:36:1:10. The above materials are placed in a high-speed mixer for 5 minutes and mixed evenly to obtain a mixed material.

[0066] Sodium pyrophosphate and polyethylene glycol 400 are weighed as dispersants, wherein the total mass of sodium pyrophosphate and polyethylene glycol 400 is 3% of the total mass of the above-mentioned uniformly mixed mixture, and the mass ratio of sodium pyrophosphate to polyethylene glycol 400 is 1:1. The mixture and the dispersant are mixed again for 2 minutes, and then placed in a twin-screw extruder for heating and melting. After extrusion, the mixture is water-cooled, stretched and pelletized, and dried at 95°C to obtain a nylon 66 material.

[0067] The operating parameters of the twin-screw extruder are set as follows: the temperatures of zones one to eight of the twin-screw extruder are set to 360°C, 365°C, 375°C, 370°C, 375°C, 370°C, 375°C, 370°C, respectively, the head temperature is adjusted to 370°C, the screw speed is 90-120r / min, the feeding speed is 15r / min, and the side feeding speed is 10r / min.

[0068] Comparative Example 1

[0069] The preparation of the modified polypropylene fiber is the same as that in Example 2; polytetrafluoroethylene is not added during the preparation of the nylon 66 material, and the rest is the same as that in Example 2.

[0070] Comparative Example 2

[0071] The preparation of modified polypropylene fiber is the same as that in Example 2; in the preparation process of nylon 66 material, calcium stearate in the auxiliary agent is not added, and the rest is the same as that in Example 2.

[0072] Comparative Example 3

[0073] The preparation of modified polypropylene fiber is the same as that in Example 2; in the preparation process of nylon 66 material, calcium stearate in the auxiliary agent is replaced by magnesium stearate, and the rest is the same as that in Example 2.

[0074] Comparative Example 4

[0075] In the preparation process of nylon 66 material, no unmodified polypropylene fiber is added, and the rest is the same as in Example 2.

[0076] Performance evaluation of nylon 66 material

[0077] Thermal deformation test instrument: Changzhou Dedu Precision Instrument Co., Ltd., instrument model: TSWL-RWK thermal deformation Vicat softening point temperature tester, according to the method disclosed in ISO 75. The thermal deformation temperature of the nylon 66 materials prepared in Examples 1-5 and Comparative Examples 1-4 was tested respectively. The specific test results are as follows: Figure 1 shown.

[0078] from Figure 1 It can be understood that the addition of polytetrafluoroethylene and calcium stearate can significantly improve the thermal stability of nylon 66 materials, and the addition of modified polyester fibers has relatively little effect on the thermal stability of the prepared nylon 66 materials.

[0079] Tensile properties

[0080] The test was conducted according to ISO527-2, with a tensile speed of 15 mm / min and a test temperature of 23° C. The nylon 66 materials prepared in Examples 1-5 and Comparative Examples 1-4 were tested for their tensile strength on an electronic tensile testing machine. The specific test results are shown in Table 1.

[0081] Table 1

[0082]

[0083] According to the tensile strength test results in Table 1 above, it can be clearly found that when unmodified polypropylene fiber is compounded with nylon and other components, the tensile strength of the nylon 66 material finally prepared is significantly reduced, while although the addition of polytetrafluoroethylene and additives in Comparative Examples 1-3 is changed, the tensile strength thereof is not significantly reduced.

[0084] Acid resistance

[0085] The testing standards and methods are in accordance with the method disclosed in GB / T11547-2008. At room temperature, the samples are immersed in a 5% sulfuric acid solution for 1 week, then taken out and dried at 50°C for 2 hours to check whether the samples have the following: sticky surface; delamination, warping or other deformation; partial dissolution; the presence of easily wiped-off substances on the surface; bubbling, small pits or other similar defects, etc. If the above types of changes occur, the samples are unqualified, and if there are no abnormalities, they are qualified.

[0086] Alkali resistance

[0087] The test standard and method is carried out according to the method disclosed in GB / T11547-2008. The sample is immersed in a 5% sodium hydroxide solution for 1 week, then taken out and dried at 50°C for 2 hours to check whether it has the following: sticky surface; delamination, warping or other deformation; partial dissolution; the presence of easily wiped-off substances on the surface; bubbling, small pits or other similar defects. If the above types of changes occur, it is unqualified, and if there is no abnormality, it is qualified.

[0088] The nylon 66 materials prepared in the above-mentioned Examples 1-5 and Comparative Examples 1-4 were subjected to the above-mentioned acid resistance and alkali resistance tests, and the test results were finally recorded, as shown in the following Table 2.

[0089] Table 2

[0090] Test items Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Acid resistance qualified qualified qualified qualified qualified Surface stickiness There are small bubbles Warping Alkali resistance qualified qualified qualified qualified qualified Partially dissolved Deformation Small pit

[0091] According to the test results of acid and alkali resistance in Table 2 above, it can be found that the nylon 66 material prepared without adding polytetrafluoroethylene has serious abnormal phenomena, such as sticky surface or partial dissolution. The addition of dissolved oxygen in calcium stearate in the additive can enhance the acid and alkali resistance of nylon 66 material.

Claims

1. A method for preparing nylon 66 material, characterized in that: The preparation method of the nylon 66 material comprises the following steps: (1) placing modified polypropylene fiber, polytetrafluoroethylene, additives and nylon 66 resin in a high-speed mixer and mixing them uniformly to obtain a mixed material; (2) mixing the mixed material and dispersant mixed uniformly in step (1) again and placing them in a twin-screw extruder for extrusion granulation to obtain a nylon 66 material; The modified polypropylene fiber, polytetrafluoroethylene, additives and nylon 66 resin are calculated by weight, 40-58 parts of nylon 66 resin, 2-10 parts of polytetrafluoroethylene, 0.1-3 parts of additives, and 13-25 parts of modified polypropylene fiber; the dispersant is sodium pyrophosphate and polyethylene glycol 400, and the additives include isooctyl salicylate, diphenyl phosphate azide, 1,2-propylene glycol, mica and calcium stearate; the mass ratio of isooctyl salicylate, diphenyl phosphate azide, 1,2-propylene glycol, mica and calcium stearate is 100:1-8:15-36:0.1-1:5-10; The preparation method of the modified polypropylene fiber is: Sodium metasilicate, urea and deionized water are prepared into a mixed solution, polypropylene fiber is put into the mixed solution, and then placed in a stainless steel reactor lined with polytetrafluoroethylene at 100-120°C for 4-7 hours. After the treatment is completed, the mixture is taken out, cooled to room temperature and dried for later use.

2. The method for preparing nylon 66 material according to claim 1, characterized in that: The mass of the dispersant in step (2) is 1-3% of the mass of the mixed material.

3. The method for preparing nylon 66 material according to claim 1, characterized in that: The mass ratio of the sodium metasilicate to urea is 100:1-6.

4. The method for preparing nylon 66 material according to claim 1, characterized in that: The temperature of the twin-screw extruder is 360-375° C., the screw speed is 90-120 r / min, the feeding speed is 10-15 r / min, and the nylon 66 material is obtained by melt extrusion, water-cooling, drawing and pelletizing.

5. The nylon 66 material obtained by the method for preparing the nylon 66 material according to any one of claims 1 to 4.

6. Application of the nylon 66 material obtained according to the preparation method according to any one of claims 1 to 4 in the field of chemical equipment.